2006
DOI: 10.1159/000091538
|View full text |Cite
|
Sign up to set email alerts
|

Medical Management in Patients following Stroke and Transitory Ischemic Attack: A Comparison between Men and Women

Abstract: Study Objective: Differences between men and women in management and outcome following cerebrovascular events have been described. However, most of the differences observed have only been partially adjusted for baseline differences, or not at all. The objective of the present study was to compare acute and follow-up management between men and women after stroke and transitory ischemic attacks, adjusting for potential confounders. Design: Patients with symptoms of stroke were included at admission to one of fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 61 publications
0
9
1
2
Order By: Relevance
“…The higher prevalence of risk factors such as HT, AF, obesity, diabetes, inactivity or poor nutrition are well known in women [15,16,17] but we observed no significant differences between men and women. We cannot argue that changes in risk factor prevalence may explain the decrease in case fatality rates because these changes did not involve the incidence rates.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The higher prevalence of risk factors such as HT, AF, obesity, diabetes, inactivity or poor nutrition are well known in women [15,16,17] but we observed no significant differences between men and women. We cannot argue that changes in risk factor prevalence may explain the decrease in case fatality rates because these changes did not involve the incidence rates.…”
Section: Discussioncontrasting
confidence: 72%
“…Some differences between men and women were reported in the literature [2,15,16,17,18]. These differences may reflect differences in competing causes of death, socioeconomic status and other factors influencing death rates, such as lack of health insurance and lack of knowledge about the early warning signs of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 We observed no gender difference in the majority of outcomes after adjusting for confounding variables. However, despite controlling for age, prestroke functional status, stroke subtype, AF, and stroke severity, women were less likely to have an excellent outcome (BI Ն95), confirming the findings of others.…”
Section: Discussionmentioning
confidence: 57%
“…ome studies of gender differences in the management of acute stroke have shown that women are investigated less thoroughly 1,2 and treated less frequently with antiplatelet agents 3 and tissue plasminogen activator (tPA). 4,5 The explanation for these findings is not clear but may relate to gender differences at presentation such as age, comorbidity, prestroke functional status, and stroke severity.…”
mentioning
confidence: 99%
See 1 more Smart Citation